A kind of shrinkage-resistant acrylate grouting material, preparation method and application thereof
By using dimethylaminoethyl methacrylate and modifier in acrylate grouting materials, the problem of poor anti-dry shrinkage performance of acrylate gels is solved, and higher anti-dry shrinkage performance and anti-seepage plugging effect are achieved.
Patent Information
- Application Number
- CN202310220940.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-03-09
AI Technical Summary
The anti-shrinkage performance of existing acrylate gels is too poor, resulting in excessive shrinkage in dry environments, losing flexibility and anti-seepage and leak plugging effects.
Dimethylaminoethyl methacrylate is used as a crosslinking agent and accelerator, and modifiers such as polyethylene glycol, polyethylene glycol monomethyl ether, ethylene glycol, propylene glycol, etc. are used to improve the anti-dry shrinkage performance of acrylate grouting materials.
The anti-dry shrinkage performance of the gel is significantly improved, the water loss rate and volume shrinkage rate are reduced, so that the dried shrinkage gel still has good elasticity and anti-seepage leakage plugging effect.
Smart Images

Figure CN116285182B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical grouting, and in particular relates to an anti-shrinkage acrylate grouting material, a preparation method and application thereof. Background Art
[0002] Acrylate grouting materials have the advantages of low initial viscosity of slurry, adjustable gel time, good gel anti-seepage performance, and water absorption and expansion. They are widely used in curtain grouting. The gel of acrylate grouting materials is a hydrogel, which contains a large amount of free water, making the gel low in strength and good in flexibility. In a humid and watery environment, the gel can maintain its original properties, but in a dry environment, the water in the gel will gradually evaporate, shrink in volume, increase in strength, and deteriorate in flexibility. According to literature reports, after the acrylate gel shrinks, the water loss rate can exceed 50%, and the volume shrinkage rate can exceed 60%, becoming a transparent hard and brittle solid and losing flexibility. It can be seen that in projects using acrylic grouting materials for plugging leaks, after a long dry season, the gel is prone to excessive shrinkage and separation from the bonding surface, losing the effect of anti-seepage and plugging leaks. Although the shrunk gel can absorb water to recover and expand and squeeze to stop water, this process takes time. Without effective bonding, the squeezing effect of water absorption and expansion alone cannot resist water pressure. It is precisely because the anti-shrinkage performance of acrylate gel is too poor that the application of acrylate grouting materials in anti-seepage and leakage plugging projects is limited. Summary of the invention
[0003] In order to solve the problem that the existing acrylate gel has poor anti-shrinkage performance, which limits the application of acrylate grouting materials in anti-seepage and plugging projects, the present invention provides an anti-shrinkage acrylate grouting material, a preparation method and application thereof.
[0004] To achieve the above object, the present invention discloses the following technical solutions:
[0005] The invention discloses an anti-shrinkage acrylate grouting material, which comprises the following components by mass fraction: 15.6-22.6 parts of acrylic acid, 4.3-6.3 parts of magnesium oxide, 1.0-1.6 parts of dimethylaminoethyl methacrylate, 10.0-20.0 parts of modifier a, 2.0-5.0 parts of modifier b, 0.2-0.5 parts of initiator, 0-0.05 parts of potassium ferrocyanide and 53.0-59.3 parts of deionized water.
[0006] Furthermore, the modifier a is at least one of polyethylene glycol and polyethylene glycol monomethyl ether, and the modifier b is at least one of ethylene glycol and propylene glycol.
[0007] Furthermore, the initiator is at least one of sodium persulfate and ammonium persulfate.
[0008] Furthermore, the polyethylene glycol is at least one of PEG200, PEG400, and PEG600.
[0009] Furthermore, the molecular weight of the polyethylene glycol monomethyl ether is no more than 800.
[0010] The invention also discloses a method for preparing a shrinkage-resistant acrylate grouting material, comprising the following steps:
[0011] Step 1: acrylic acid and deionized water are mixed, and magnesium oxide is added to react under stirring to obtain a magnesium acrylate solution, and dimethylaminoethyl methacrylate is added to the magnesium acrylate solution, and the mixture is mixed to obtain a liquid A;
[0012] Step 2: Dissolve potassium ferrocyanide and initiator in distilled water, then add modifier a and modifier b to mix to obtain liquid B;
[0013] Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0014] Specifically, the composition includes the following components by mass fraction: 15.6-22.6 parts of acrylic acid, 4.3-6.3 parts of magnesium oxide, 1.0-1.6 parts of dimethylaminoethyl methacrylate, 10.0-20.0 parts of modifier a, 2.0-5.0 parts of modifier b, 0.2-0.5 parts of initiator, 0-0.05 parts of potassium ferrocyanide, and 53.0-59.3 parts of deionized water.
[0015] Specifically, the modifier a is at least one of polyethylene glycol and polyethylene glycol monomethyl ether, and the modifier b is at least one of ethylene glycol and propylene glycol;
[0016] The initiator is at least one of sodium persulfate and ammonium persulfate.
[0017] Specifically, the temperature of the reaction system in step 1 does not exceed 50° C., and the reaction time is 0.5 to 2 hours.
[0018] The invention also discloses application of an anti-shrinkage acrylic acid salt grouting material in anti-seepage and leakage plugging engineering of deformation joints.
[0019] Compared with the prior art, the present invention has the following technical effects:
[0020] The present invention innovatively uses dimethylaminoethyl methacrylate in an acrylate grouting material system. The material is both a crosslinking agent and a accelerator, so that the acrylate gel has super high elasticity, and the elongation at break can exceed 1200%. At the same time, the gel has better water absorption and expansion properties, and the gel has better elasticity before it is completely dried. Polyethylene glycol, polyethylene glycol monomethyl ether, ethylene glycol, propylene glycol and the like are used to modify the acrylate grouting material, and the anti-shrinkage performance of the gel is greatly improved without significantly increasing the viscosity of the slurry, the water retention of the gel is increased, the water loss rate and the volume shrinkage rate are reduced, and the gel after shrinkage still has excellent elasticity and can adapt to the dynamic changes of cracks.
[0021] The present invention is further described in detail below in conjunction with specific implementation modes. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Attached Figure 1 This is a schematic diagram of sample preparation for the anti-dry-wet cycle test of the present invention;
[0023] Attached Figure 2 is the change of water loss rate of the gel of the present invention with drying time; DETAILED DESCRIPTION
[0024] Any structural modification, proportional change or size adjustment should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention.
[0025] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. All equivalent changes made on the basis of the technical scheme of this application fall within the protection scope of the present invention.
[0026] Acrylate gel is a high molecular polymer network structure with long carbon chains as the skeleton and multivalent metal ions and cross-linking agent molecules as cross-linking points. A large amount of water is filled in the polymer network as a plasticizer, which greatly reduces the interaction between polar groups and molecular chains. The distance between molecular chains is large and the molecular chains have a lot of space to move. Therefore, the gel has good flexibility. When the water evaporates, the distance between molecular chains decreases, the interaction between polar groups and molecular chains becomes stronger, the movement of molecular chains is gradually restricted, and the gel gradually loses its flexibility.
[0027] The present invention uses dimethylaminoethyl methacrylate in the acrylate grouting material system. Its structure contains one C=C that can participate in free radical polymerization and one tertiary amine structure (CH3)2-NCH2 that can play an initiating role. After polymerization, a "T"-shaped crosslinking point is formed, the crosslinking density is low, and the molecular chain has strong mobility, so the gel has super high elasticity. The traditional crosslinking agent contains two C=Cs, and after polymerization, an "I"-shaped crosslinking point is formed, the crosslinking density is high, and the molecular chain has weak mobility, so the gel has low elasticity.
[0028] The present invention uses polyethylene glycol, polyethylene glycol monomethyl ether, ethylene glycol, propylene glycol and the like to modify the acrylate grouting material. On the one hand, because of the high boiling point, the acrylate grouting material is basically non-volatile at room temperature, and the good water solubility, it can replace part of the water as a plasticizer to fill the polymer network. On the other hand, because the ether group and hydroxyl group contained in the acrylate grouting material have a relatively strong attraction to water molecules, it can play a certain role in water retention and reduce the volatilization of water. The above dual effects can greatly reduce the shrinkage of the acrylate gel, thereby allowing the gel to maintain good flexibility.
[0029] The method for preparing the shrinkage-resistant acrylate grouting material of the present invention comprises the following steps:
[0030] Step 1: acrylic acid and deionized water are mixed, and magnesium oxide is added to react under stirring to obtain a magnesium acrylate solution, and dimethylaminoethyl methacrylate is added to the magnesium acrylate solution, and the mixture is mixed to obtain a liquid A; the temperature of the reaction system does not exceed 50° C., and the reaction time is 0.5 to 2 hours.
[0031] Step 2: Dissolve potassium ferrocyanide and initiator in distilled water, then add modifier a and modifier b to mix to obtain liquid B;
[0032] Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0033] Example 1
[0034] This embodiment discloses a method for preparing an anti-shrinkage acrylate grouting material. The initiator is sodium persulfate, the modifier a is polyethylene glycol, PEG400, and the modifier b is propylene glycol.
[0035] The following steps are involved:
[0036] Step 1: 156 g of acrylic acid and 250.6 g of deionized water were mixed, and 43 g of magnesium oxide was added in batches under stirring, and the temperature of the reaction system was controlled not to exceed 50° C. by cooling water. After all the magnesium oxide was added, the reaction was carried out for 1 hour to obtain a magnesium acrylate solution, and 16 g of dimethylaminoethyl methacrylate was added to the magnesium acrylate solution, and the mixture was mixed to obtain a liquid A;
[0037] Step 2: Dissolve 0.5 g potassium ferrocyanide and 5 g sodium persulfate in 279.4 g distilled water, then add 200 g PEG200 and 50 g propylene glycol to obtain liquid B;
[0038] Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0039] Embodiment 2:
[0040] In this embodiment, the initiator is sodium persulfate, the modifier a is a mixture of PEG400 and PEG200, and the modifier b is propylene glycol.
[0041] The following steps are involved:
[0042] Step 1: 191 g of acrylic acid and 306.4 g of deionized water were mixed, and 53 g of magnesium oxide was added in batches under stirring, and the temperature of the reaction system was controlled not to exceed 50° C. by cooling water. After all the magnesium oxide was added, the reaction was carried out for 1 hour to obtain a magnesium acrylate solution, and 12 g of dimethylaminoethyl methacrylate was added to the magnesium acrylate solution, and the mixture was mixed to obtain a liquid A;
[0043] Step 2: Dissolve 0.2 g potassium ferrocyanide and 4 g sodium persulfate in 253.6 g distilled water, then add 100 g PEG200, 50 g PEG400 and 30 g propylene glycol to obtain liquid B;
[0044] Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0045] Embodiment 3:
[0046] In this embodiment, the initiator is sodium persulfate, the modifier a is PEG200, and the modifier b is ethylene glycol.
[0047] The following steps are involved:
[0048] Step 1: 191 g of acrylic acid and 306.4 g of deionized water were mixed, and 53 g of magnesium oxide was added in batches under stirring, and the temperature of the reaction system was controlled not to exceed 50° C. by cooling water. After all the magnesium oxide was added, the reaction was carried out for 1 hour to obtain a magnesium acrylate solution, and 12 g of dimethylaminoethyl methacrylate was added to the magnesium acrylate solution, and the mixture was mixed to obtain a liquid A;
[0049] Step 2: Dissolve 3 g of sodium persulfate in 253.6 g of distilled water, then add 100 g of PEG200 and 50 g of propylene glycol to obtain liquid B;
[0050] Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0051] Embodiment 4:
[0052] In this embodiment, the initiator is ammonium persulfate, the modifier a is PEG200, and the modifier b is propylene glycol.
[0053] The following steps are involved:
[0054] Step 1: 226 g of acrylic acid and 362.3 g of deionized water were mixed, and 63 g of magnesium oxide was added in batches under stirring, and the temperature of the reaction system was controlled not to exceed 50° C. by cooling water. After all the magnesium oxide was added, the reaction was carried out for 1 hour to obtain a magnesium acrylate solution, and 12 g of dimethylaminoethyl methacrylate was added to the magnesium acrylate solution, and the mixture was mixed to obtain a liquid A;
[0055] Step 2: Dissolve 2 g of sodium persulfate in 216.7 g of distilled water, then add 100 g of PEG200 and 20 g of propylene glycol to obtain liquid B;
[0056] Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0057] Comparative Example 1:
[0058] This comparative example replaces dimethylaminoethyl methacrylate with polyethylene glycol diacrylate, and does not add modifier a and modifier b, including:
[0059] Step 1: 191 g of acrylic acid and 306.4 g of deionized water were mixed, and 53 g of magnesium oxide was added in batches under stirring to react, and the temperature of the reaction system was controlled not to exceed 50° C. by cooling water. After all the magnesium oxide was added, the reaction was carried out for 1 hour to obtain a magnesium acrylate solution, and 10 g of polyethylene glycol diacrylate (molecular weight of about 600) and 10 g of triethanolamine were added to the magnesium acrylate solution, and the mixture was mixed to obtain a liquid A;
[0060] Step 2: Dissolve 3 g of sodium persulfate in 426.6 g of distilled water to obtain liquid B;
[0061] Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0062] Comparative Example 2:
[0063] This comparative example replaces dimethylaminoethyl methacrylate with polyethylene glycol diacrylate, including:
[0064] Step 1: 191 g of acrylic acid and 306.4 g of deionized water were mixed, and 53 g of magnesium oxide was added in batches under stirring to react, and the temperature of the reaction system was controlled not to exceed 50° C. by cooling water. After all the magnesium oxide was added, the reaction was carried out for 1 hour to obtain a magnesium acrylate solution, and 10 g of polyethylene glycol diacrylate (molecular weight of about 600) and 10 g of triethanolamine were added to the magnesium acrylate solution, and the mixture was mixed to obtain a liquid A;
[0065] Step 2: Dissolve 3 g of sodium persulfate in 276.6 g of distilled water, then add 100 g of PEG200 and 50 g of ethylene glycol to obtain liquid B;
[0066] Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0067] Comparative Example 3
[0068] This comparative example does not add modifier a and modifier b, and includes:
[0069] Step 1: 191 g of acrylic acid and 306.4 g of distilled water were mixed evenly, and 53 g of magnesium oxide was added in batches under stirring, and the temperature of the reaction system was controlled not to exceed 50° C. by using cooling water, and after all the magnesium oxide was added, the reaction was carried out for 1 hour to obtain a magnesium acrylate solution, and 10 g of dimethylaminoethyl methacrylate was added to the magnesium acrylate solution, and the mixture was mixed evenly to obtain a liquid A;
[0070] Step 2: Dissolve 3 g of sodium persulfate in 436.6 g of distilled water and mix well to obtain liquid B;
[0071] Step 3: Evenly mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
[0072] Effect Example
[0073] The initial viscosity of the slurry, gel time, compressive strength of the sand-fixing body, and water expansion rate of the acrylate grouting materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested according to JC / T1041-2007. The test results are shown in Table 1.
[0074] Gel water loss rate test method: cast acrylate grouting material into a 100mm×20mm×10mm cavity, cover it with plastic wrap after gelation to prevent evaporation of water in the gel, demould after 1d, cut it into 20mm×20mm×10mm specimens, weigh the initial mass of the specimens, and then place the specimens in an environment of (23±2)℃ and humidity (50±10)% to dry, weigh the mass of the specimens after drying for a certain period of time, and calculate the water loss rate.
[0075] Test method for volume shrinkage of gel after water loss: Use a vernier caliper to accurately measure the size of a 20mm×20mm×10mm gel sample to obtain the initial volume of the gel, then measure the size of the sample after drying for a certain period of time in an environment of (23±2)℃ and humidity (50±10)%, obtain the volume of the gel after drying, and calculate the volume shrinkage.
[0076] Gel break elongation test method: prepare a silicone mold with a cavity size of 100mm×20mm×10mm and a 40mm×20mm×10mm standard mortar block, put two mortar blocks into the cavity of the silicone mold to form a 20mm×20mm×10mm cavity in the middle, pour acrylate grouting material into it, cover it with plastic wrap after gelation to prevent water evaporation in the gel, demold it together with the mortar block after 1 day to obtain a tensile specimen, and then use WDW3020 micro-controlled electronic universal testing machine for tensile testing. The elongation when the gel breaks or debonds from the standard mortar block is the elongation at break.
[0077] Gel anti-drying and wetting cycle test: Prepare a silicone mold with a cavity size of 100mm×100mm×10mm, 100mm×40mm×10mm and 20mm×20mm×10mm standard mortar blocks, and place two 100mm×40mm×10mm and 20mm×20mm×10mm standard mortar blocks as shown in the figure. Figure 1 As shown, the sample was placed in the cavity of the silicone mold to form a 60mm×20mm×10mm cavity, and the acrylate grouting material was cast into it. After gelation, it was covered with plastic wrap to prevent the evaporation of water in the gel. After 1 day, it was demoulded together with the mortar block, dried for 30 days in an environment of (23±2)℃ and humidity of (50±10)%, and then immersed in water for 7 days as a dry-wet cycle. After one dry-wet cycle, the cracks in the gel and the separation from the mortar block were observed.
[0078] Figure 2 The water loss rate of the gels in Example 3 and Comparative Examples 1 to 3 varies with drying time. It can be seen that the gels lose water faster in the first 7 days, and reach equilibrium after 15 days and no longer lose water. The water loss rates of Example 3 and Comparative Example 2 are similar, and the water loss rates of Comparative Example 1 and Comparative Example 3 are similar, with the former being significantly lower than the latter, indicating that replacing the cross-linking agent has no significant effect on the water loss rate. The use of the modifier of the present invention can significantly reduce the water loss rate and increase the anti-shrinkage performance.
[0079] Table 1 Properties of acrylate grouting materials
[0080]
[0081]
[0082] Comparative Example 1 uses an acrylate containing two C=C double bonds as a crosslinking agent, which is currently the main acrylic grouting material in China. As can be seen from Table 1, the viscosity of the acrylic grouting material of the present invention is not much different from that of Comparative Example 1, and the gel strength and water expansion rate are higher, especially the elongation at break is much higher than that of Comparative Example 1. By comparing the elongation at break of Comparative Example 1 and Comparative Example 3, it can be seen that the present invention uses dimethylaminoethyl methacrylate as a crosslinking agent and accelerator to replace conventional acrylate crosslinkers and accelerators, so that the acrylic grouting material has super high elasticity. After the gel of the present invention is dried to equilibrium, the water loss rate and volume shrinkage rate are significantly lower than those of Comparative Example 1. Although the elongation at break has decreased, it is still very high. The gel after shrinkage has good elasticity, while the gel of Comparative Example 1 has a low elongation at break, and directly becomes brittle after shrinkage.
[0083] In the dry-wet cycle test, due to the fixing effect of the mortar block, the gel body cannot shrink freely in the width and length directions when it shrinks, which is similar to the actual situation in the plugging project. From the test results, it can be seen that after the dry-wet cycle, the gel body of the acrylic grouting material of the present invention has no cracks and does not separate from the mortar block. This is because the gel body of the present invention still has good elasticity after shrinking, and can compensate for its shrinkage in the width and length directions through its own stretching under the shrinkage internal stress; while the gel body of comparative example 1 has cracks and separates from the mortar block after the dry-wet cycle. This is because the elasticity of the gel body of comparative example 1 is poor, and it becomes a brittle solid after shrinking, and brittle cracking and debonding occur under the action of shrinkage internal stress. In summary, the comprehensive performance and shrinkage resistance of the acrylate grouting material of the present invention are significantly better than the main acrylic grouting materials currently in China.
[0084] In the above-listed embodiments, the purpose, technical solutions and advantages of the present invention are further described in detail. It should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0085] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0086] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0087] In addition, the various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the content invented by the present disclosure.
Claims
1. An anti-shrinkage acrylate grouting material, characterized in that: The anti-shrinkage acrylate grouting material comprises the following components by mass fraction: 15.6-22.6 parts of acrylic acid, 4.3-6.3 parts of magnesium oxide, 1.0-1.6 parts of dimethylaminoethyl methacrylate, 10.0-20.0 parts of modifier a, 2.0-5.0 parts of modifier b, 0.2-0.5 parts of initiator, 0-0.05 parts of potassium ferrocyanide, and 53.0-59.3 parts of deionized water; The modifier a is at least one of polyethylene glycol and polyethylene glycol monomethyl ether, and the modifier b is at least one of ethylene glycol and propylene glycol.
2. The shrinkage-resistant acrylate grouting material according to claim 1, characterized in that: The initiator is at least one of sodium persulfate and ammonium persulfate.
3. The shrinkage-resistant acrylate grouting material according to claim 1, characterized in that: The polyethylene glycol is at least one of PEG200, PEG400 and PEG600.
4. The shrinkage-resistant acrylate grouting material according to claim 1, characterized in that: The molecular weight of the polyethylene glycol monomethyl ether is no more than 800.
5. The method for preparing the shrinkage-resistant acrylate grouting material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: acrylic acid and deionized water are mixed, and magnesium oxide is added to react under stirring to obtain a magnesium acrylate solution, and dimethylaminoethyl methacrylate is added to the magnesium acrylate solution, and the mixture is mixed to obtain a liquid A; Step 2: Dissolve potassium ferrocyanide and the initiator in deionized water, and then add modifier a and modifier b to mix to obtain liquid B; Step 3: Mix liquid A and liquid B to obtain shrinkage-resistant acrylate grouting material.
6. The method for preparing the shrinkage-resistant acrylate grouting material according to claim 5, characterized in that: The composition includes the following components by mass fraction: 15.6-22.6 parts of acrylic acid, 4.3-6.3 parts of magnesium oxide, 1.0-1.6 parts of dimethylaminoethyl methacrylate, 10.0-20.0 parts of modifier a, 2.0-5.0 parts of modifier b, 0.2-0.5 parts of initiator, 0-0.05 parts of potassium ferrocyanide and 53.0-59.3 parts of deionized water.
7. The method for preparing the shrinkage-resistant acrylate grouting material according to claim 5, characterized in that: The modifier a is at least one of polyethylene glycol and polyethylene glycol monomethyl ether, and the modifier b is at least one of ethylene glycol and propylene glycol; The initiator is at least one of sodium persulfate and ammonium persulfate.
8. The method for preparing the shrinkage-resistant acrylate grouting material according to claim 5, characterized in that: The temperature of the reaction system in step 1 does not exceed 50° C., and the reaction time is 0.5 to 2 hours.
9. Use of the shrinkage-resistant acrylate grouting material according to any one of claims 1 to 4 in anti-seepage and plugging engineering of deformation joints.
Citation Information
Patent Citations
Acrylate aqueous solution grouting material and preparation method thereof
CN108299599A
Associative acrylate grouting material as well as preparation method and application thereof
CN114539465A